2002
DOI: 10.1002/jmv.10212
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytomegalovirus DNA in human placenta

Abstract: Although human cytomegalovirus (CMV) is one of the most common causes of viral intrauterine and perinatal infection, its distribution in the placenta is poorly understood. The purpose of this study was to determine the frequency of CMV DNA positivity in placentas, to demonstrate the localization of the viral genome, and to identify the clinical features related to placental CMV. A total of 254 placentas from 231 mothers were investigated, and the maternal serum CMV immunoglobulin antibodies were measured. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
(17 reference statements)
3
14
0
Order By: Relevance
“…Other studies on cases with previous immunity against the virus showed nearly similar results [21]. Kumazaki et al [10] reported that the CMV genome was detected by PCR analysis in placentas, not only on the maternal side, but also in the villi of seropositive women.…”
Section: Discussionsupporting
confidence: 50%
“…Other studies on cases with previous immunity against the virus showed nearly similar results [21]. Kumazaki et al [10] reported that the CMV genome was detected by PCR analysis in placentas, not only on the maternal side, but also in the villi of seropositive women.…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, 69% of first-and secondtrimester placental biopsy samples from uncomplicated pregnancies tested positive for CMV DNA. Others have reported CMV in cervical and placental samples in late gestation, with higher detection rates in abnormal pregnancies [1,39]. Differences in detection rates may be due to the sensitivity of the methods used.…”
Section: Discussionmentioning
confidence: 88%
“…Of those TH1 cytokine IL-2 plays a key role in regulating the balance between immunity and tolerance. 35,43,44 In this study, preeclamptic women seropositive for CMV-IgG, the IL-2 concentration was elevated but statistically not significant in comparison with seronegative CMV-IgG level (P > 0.05). Results obtained in this study indicated that the mean concentration of IL-2 was significantly higher in normotensive women seropositive for CMV-IgG as compared to seronegative group (P < 0.05).…”
Section: Discussionmentioning
confidence: 51%